Whistle in the dark - Healey, Emma (Leicestershire; ISIS, 2019)
Jen is at her wits$1 (Bend. Her fifteen-year-old daughter has just been found after going missing: four days lost and alone in the desolate countryside. Lana won$1 (Bt talk about it. The police think the case is closed. But Jen can$1 (Bt leave it alone. Lana is acting strangely: she stops going to school, and sleeps with the lights on. With her daughter increasingly becoming a stranger, Jen is sure the answer lies in those four missing days. But will Lana ever reveal what happened?s